2-Iodo benzoic acid: An unconventional precursor for the one pot multi-component synthesis of quinoxaline using organo Cu (II) catalyst. Issue 41 (10th October 2018) - Saha, Bittu; Mitra, Bijeta; Brahmin, Dhiraj; Sinha, Biswajit; Ghosh, Pranab
Graphical abstract: Highlights: Use of 2-iodo benzoic acid, an alternative starting material. Exploration of a benign Cu(II) organo catalyst. Easy reaction set-up. Moderate to high yield. Functional group tolerance. Abstract: This is the first reported, unconventional, efficient strategy for the synthesis of quinoxaline from 2 to iodo benzoic acid and sodium azide in presence of organo Cu (II) catalyst. Herein, a very simple, versatile one pot multi-component protocol for the synthesis of biologically active compound, quinoxaline has been described via Schmidt reaction and the nucleophilic substitution reaction. The isolated compounds were characterized by 1H NMR, 13C NMR. Our reported organo catalyst was characterized by single crystal XRD, SEM.